Cancer control in the Pacific: big challenges facing small island states. Issue 9 (September 2019) - Sarfati, Diana; Dyer, Rachel; Sam, Filipina Amosa-Lei; Barton, Michael; Bray, Freddie; Buadromo, Eka; Ekeroma, Alec; Foliaki, Sunia; Fong, James; Herman, Josephine; Huggins, Linda; Maoate, Kiki; et al.
Summary: This Series paper describes the current state of cancer control in Pacific island countries and territories (PICTs). PICTs are diverse but face common challenges of having small, geographically dispersed, isolated populations, with restricted resources, fragile ecological and economic systems, and overburdened health services. PICTs face a triple burden of infection-related cancers, rapid transition to lifestyle-related diseases, and ageing populations; additionally, PICTs are increasingly having to respond to natural disasters associated with climate change. In the Pacific region, cancer surveillance systems are generally weaker than those in high-income countries, and patients often present at advanced cancer stage. Many PICTs are unable to provide comprehensive cancer services, with some patients receiving cancer care in other countries where resources allow. Many PICTs do not have, or have poorly developed, cancer screening, pathology, oncology, surgical, and palliative care services, although some examples of innovative cancer planning, prevention, and treatment approaches have been developed in the region. To improve cancer outcomes, we recommend prioritising regional collaborative approaches, enhancing cervical cancer prevention, improving cancer surveillance and palliative care services, and developing targeted treatment capacity in the region.